Analisis Nilai Moral dalam Cerpen “Handuk Kumal Kang Gudhal” Karya Ribut Acahwadi - Eva Oktaviana Sari; Yolanda Tania (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to describe and analyze the moral values ​​contained in the short story “Towel Kumal Kang Gudhal” by Ribut Acahwadi. The approach used in this study is descriptive qualitative. The main data source comes from the short story which was published in the online media Ruang Sastra on June 18, 2023. Data collection techniques were carried out through reading activities, recording, and literature studies. To ensure the validity of the data, data and theory triangulation methods were used. The data analysis process includes four stages, namely data collection, identification, data reduction, and drawing and verifying conclusions. The results of the analysis show that this short story contains three forms of moral values, namely: 1) morals related to human relationships with themselves, such as patience, responsibility, and honesty; 2) morals concerning relationships between humans, such as caring and respect; and 3) morals related to human relationships with God, which are reflected through spiritual beliefs and beliefs.